Penyuluhan Fisioterapi mengenai Stimulasi OralMotorsensori untuk Peningkatan Nafsu Makan pada Posyandu Anak di RW 02 Kelurahan Kota Lama, Kota Malang - Nazwa Kamilatunnisa; Safun Rahmanto (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2025)
Physiotherapy plays an important role in promotive and preventive efforts through education for the community, including children’s health posts (posyandu). Children aged 1–5 years often experience eating difficulties that reduce appetite, increasing the risk of malnutrition and growth retardation. Low appetite is often related to oral-motor function disorders, such as difficulty chewing or swallowing. This activity aimed to increase mothers’ knowledge about oral-motor-sensory stimulation as an effort to improve children’s appetite. The community service program was conducted at Posyandu RW 02, Kota Lama Subdistrict, Malang City, involving 15 mothers or caregivers of toddlers. The method included physiotherapy counseling using interactive discussions and poster media, with knowledge evaluation through pre-test and post-test. The results showed a significant improvement in participants’ knowledge, from 0% in the pre-test to 85% in the post-test. This counseling effectively enhanced mothers’ understanding and practical skills in performing oral-motor-sensory stimulation independently at home. With regular implementation, this stimulation is expected to increase children’s appetite, improve nutritional status, and support optimal growth and development. Moreover, it reinforces the role of physiotherapy in preventing nutritional problems and improving the quality of life of children from an early age.